ANALISIS MANFAAT BANTUAN KELOMPOK USAHA BERSAMA (KUBE) TAHUN 2022–2024 PROVINSI SULAWESI TENGAH - Damayanti Damayanti; Edhi Taqwa; Yohan Yohan; Patta Tope; Yunus Sading (Ensiklopedia of Journal, 2026)
Poverty in Central Sulawesi remains well above the national average, prompting the Joint Business Group (KUBE) programme as a community empowerment strategy. This study analyses the success level and continuation feasibility of KUBE assistance in Donggala Regency and Palu City for 2022–2024. Using a descriptive mixed-methods design with total sampling of ten groups, data were analysed through a seven-criterion scoring method and utility theory. Results show an average score of 2.74 out of 5 (sufficient category), with group income rising by 31.5% on average. Social-participatory dimensions scored highest, while economic-institutional dimensions (cooperative and savings) were weakest. The programme is feasible to continue with strengthened institutional capacity and mentoring.Keywords: empowerment; joint business group; poverty alleviation; scoring method; utility